Quantum dots genosensor for Her2/Neu oncogene - a breast cancer biomarker - Fuku, Xolile Godfrey (University of the Western Cape, 2015)
Philosophiae Doctor - PhD === The human epidermal growth factor receptor (HER)-family of receptor tyrosine kinases; human epidermal growth factor receptor 1, human epidermal growth factor receptor 2, human epidermal growth factor receptor 3 and human epidermal growth factor receptor 4 (EGFR/HER1, ErbB2/HER2, ErbB3/HER3, and ErbB4/HER4) plays a major role in the pathogenesis of many solid tumours, in approximately 25 - 30% of breast cancers. Breast cancer is the second most common type of cancer and affects around 3000 women annually in South Africa alone. While the benefits of treatment and cancer progress to enhance therapeutic effectiveness for the patient are well documented, it is also important to employ or fabricate methods in which cancer can be screened at an early stage. A number of gene and protein based biomarkers have shown potential in the early screening of cancer. One specific biomarker that is over-expressed in 20 - 30% of human breast cancers is the human epidermal growth factor receptor 2 (Her2/neu). Several methods have been developed for detection of Her2/neu oncogene including immunohistochemistry (IHC), enzyme-linked immunosorbent assay (ELISA), fluorescent in situ hybridisation (FISH) and polymerase chain reaction(PCR). However, these methods are subjected to interference problem. For these reasons an ultrasensitive, cheap and easy to use genosensor has been developed for early detection of the Her2/neu oncogene using electrochemical and spectroscopic methods. Due to their high surface-to-volume ratio, electro-catalytic activity as well as good biocompatibility and novel electron transport properties quantum dots are highly attractive materials for ultra-sensitive detection of biological macromolecules via bio-electronic or bio-optic devices. In this study a quantum dots (QDs)-based genosensor was developed in which Ga2Te3-based quantum dots were synthesised using a novel aqueous solution approach by mixing 3-mercaptopropionic acid (3MPA)-capped gallium metal precursor with reduced tellurium metal. The morphological, compositional and structural characterisation of the QDs was investigated prior to their utilization in DNA sensor construction.